Growth Response of Palm Seedlings (Elaeis Guineensis Jacq.) to The Provision of Palm Waste Compost in The Main Nursery - Anis Tatik Mariyani; Antonius Sianipar; Sarman S (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Introduction/Main Objectives: This research aims to see the response of oil palm seedlings to the provision of palm oil waste compost in the main nursery and to obtain the best dose of palm oil waste compost to increase the growth of oil palm seedlings (Elaeis guineensis Jacq.) in the Main Nursery. Research Methods: This research was conducted using a Randomized Blocked Design (RBD) by administering several doses of palm oil waste compost with the following treatment levels: p0 =Without Composting Palm Oil Waste, p1 =500 g palm oil waste compost/polybag, p2 =600 g of palm oil waste compost/polybag, p3 =700 g of palm oil waste compost/polybag, p4 =800 g of palm oil waste compost/polybag, and p5 =900 g of palm oil waste compost/polybag. The variables observed were increase in seedling height, increase in number of leaves, tuber diameter, total leaf area, shoot dry weight, root dry weight, root shoot ratio. Finding/Results: The research results show that providing palm oil waste compost and NPKMg fertilizer was able to respond to the growth of 6 month oil palm seedlings in the main nursery on the variables of root dry weight, shoot dry weight and root shoot ratio and the treatment dose of 600 g of palm oil waste compost gave the best average growth 6 month old oil palm seedlings in the main nursery.